SUSU KUDA SUMBAWA KHAS INDONESIA BAHAN KOSMETIK ANTIBAKTERI JERAWAT (Staphylococcus epidermidis) - Fauzia Nur Laili; Erna Prawita Setyowati; Susi Iravati (Faculty of Pharmacy, Universitas Gadjah Mada, 2014)
Sumbawa horse milk is one of pure milk of wild horses farmed by organic farmers in the island of Sumbawa, West Nusa Tenggara, Indonesia. The communities claim that milk has many benefits. In this study Sumbawa horse milk was effective as an antibacterial against Staphylococcus epidermidis (one of the bacteria caused acne). Antibacterial activity test performed by spread plate method and quantified by standard plate count. Percentage of the number of colonies after contact with Sumbawa horse milk for 5 minutes (used acid control). The result of 25% is 99.96%, 12.5% is 99.99%, 6.25% is 99, 67% and 3.125% is 99.73%. This suggests that Sumbawa horse milk has good antibacterial activity until 3.125%.